(untitled) (Journal of Educational Sciences, 2020)
In this article the theoretical materials in accordance with Bloom’s taxonomis explored in which tasks are classified into 6 levels: the first level is “Knowledge”, the second level is “Understanding”, the third level is “Application”, the fourth level is “Analysis”, the fifth level is “ Synthesis “and the sixth level is “Assessment”. Theoretical materials are dealt with in accordance with Bloom’s taxonomy of the discipline “History of Education”. The assessment criteria form the subject, instrumental and interpersonal competences. As the discipline in subject competence the student owned the pedagogical technology in the high level; the student also can use interactive forms of training, he knows tasks selection criteria for differentiated instruction with instrumental competence. The student is able to use interactive forms of learning: dialogue, debates, discussions, work in pairs, in groups, and can use the parts retrieval, problem, research methods, project methods also he is able to search for, analyze and select the desired material on the topic of study. Self-respect and respect of others is produced with interpersonal competencies; the student can work in a team and willingness to make a collective decision; the student has ability to take responsibility for the decision, the manifestation of personal enthusiasm and the ability to work in a team. Key words: Bloom’s Taxonomy, assessment criteria, subject competence, instrumental competence, interpersonal competence, the reflection of the students, teacher’s reflection.